2021
DOI: 10.18235/0003344
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Remote Learning in Secondary Education: Evidence from Brazil during the Pandemic

Abstract: The goal of this paper is to document the pedagogic impacts of the remote learning strategy used by an state department of education in Brazil during the pandemic. We found that dropout risk increased by 365% under remote learning. While risk increased with local disease activity, most of it can be attributed directly to the absence of in-person classes: we estimate that dropout risk increased by no less than 247% across the State, even at the low end of the distribution of per capita Covid-19 cases. Average s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…En otros países, sobre todo del Primer Mundo, ya se están evaluando las consecuencias del cese de clases presenciales. La conclusión preliminar es esta: A más tiempo de pérdida de clases presenciales, se pierden más aprendizajes (Engzell et al, 2021;Maldonado & De Witte, 2021;Tomasik et al, 2021;Lichand et al, 2021;Donnelly & Patrinos, 2021). Una observación es importante: estos estudios, realizados en Países Bajos, Suiza, Brasil, Estados Unidos, Alemania y Australia, se centran en el cese de clases por algunas semanas, después de las cuales, se retomaron las clases, con las debidas medidas de protección.…”
Section: Discussionunclassified
“…En otros países, sobre todo del Primer Mundo, ya se están evaluando las consecuencias del cese de clases presenciales. La conclusión preliminar es esta: A más tiempo de pérdida de clases presenciales, se pierden más aprendizajes (Engzell et al, 2021;Maldonado & De Witte, 2021;Tomasik et al, 2021;Lichand et al, 2021;Donnelly & Patrinos, 2021). Una observación es importante: estos estudios, realizados en Países Bajos, Suiza, Brasil, Estados Unidos, Alemania y Australia, se centran en el cese de clases por algunas semanas, después de las cuales, se retomaron las clases, con las debidas medidas de protección.…”
Section: Discussionunclassified
“…Differences in policy content by subnational governments in Brazil, as well as variation in the implementation of policies, suggest that the COVID-19 pandemic will widen learning gaps in various student populations in the country. An analysis of learning loss in São Paulo state, for example, found that early in the pandemic, students studying remotely learned 27.5% on average of what they were expected to, using in-person learning as a reference (Lichand et. al 2021).…”
Section: Subnational Variation In Brazilmentioning
confidence: 99%
“…A study in Uganda found that while older children aged 12-14 years showed some improvement in basic skills, the share of 8-year-old children who were non-readers increased from 33% in 2018 to 51% in 2021, and the share who were non-numerate increased from 22% to 31% (Uwezo Uganda, 2021). In rural Karnataka, India (Annual Status of Education Report, 2021), in São Paulo, Brazil (Lichand et al, 2021), and in Kenya (Whizz Education, 2021), larger losses were observed among students in earlier grades than in later grades.…”
Section: Younger Studentsmentioning
confidence: 99%